Multifunctional residential complexes in the urban structure of Karlsruhe (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
In the context of contemporary urbanization processes, climate change, and thegrowing demand for high-quality and affordable housing, European cities are facing the need totransition toward sustainable and integrated models of spatial development. One of the key forms ofsuch transformation is multifunctional residential complexes that combine housing, public spaces,service facilities, and elements of green infrastructure. The aim of this study is to conduct acomprehensive analysis of the architectural and urban planning foundations underlying theformation of contemporary residential complexes and multifunctional residential ensembles in thecity of Karlsruhe as key elements of a sustainable urban environment, as well as to determine theirrole in the transformation of the spatial structure, functional organization, and quality of theresidential environment within the framework of compact and integrated urban development.The study applies a comprehensive architectural and urban-planning approach, including ananalysis of the urban structure of Karlsruhe, a typological study of residential and multifunctionalcomplexes, and an examination of key projects—BadenCarré, Rintheimer Feld, and EttlingerTor. Particular attention is paid to issues of multifunctionality, the organization of public spaces,the integration of social infrastructure, and the application of sustainable development principles.As a result of the study, it has been established that contemporary residential complexes inKarlsruhe form a qualitatively new type of organization of urban residential development based onhigh density, multifunctionality, and orientation toward public transport. Such complexes contributeto reducing transport dependency, improving the quality of the residential environment, andenhancing the resilience of the urban structure. The findings confirm that the experience ofKarlsruhe can be regarded as a promising model for the transformation of residential developmentin European and post-socialist cities.
Keywords: Karlsruhe; residential complexes; multifunctional development; sustainable development; urban structure; block development